Ruta avituristica en el cantón Sigchos de la provincia de Cotopaxi. - Flores Muñoz, Jefferson Luis (2024)
The Ecuadorian countryside is renowned for its vast biodiversity on a global scale, making it a prime destination for birdwatching. However, in the Sigchos canton, the exploitation of bird biodiversity resources is limited due to the local population's lack of awareness regarding the opportunities presented by birdwatching activities. This research aims to design a birdwatching route within the Sigchos canton, considering its five parishes and offering economic alternatives to the population through the creation of a bird route. A diagnostic of the study area was conducted, establishing the canton's status and its various climatic zones, which contribute to a diverse range of bird species. Fifteen natural tourist attractions with significant biodiversity were identified for definitive observation zones. Subsequently, an inventory of species was compiled through field visits and direct observation methods, utilizing tools such as E-bird and the Bioweb of the Pontifical Catholic University of Ecuador, resulting in the documentation of 72 taxonomic species, including their order, family, scientific name, English name, and conservation status. Definitive observation zones were identified using discrimination tables, considering factors like tourist infrastructure, road conditions, and accessibility, alongside the Sorensen index to gauge species similarity across different sighting points. This facilitated the development of a birdwatching route comprising six observation zones within a 189km radius from Latacunga city, offering both full-day and two-day, one-night tour options. The intention is for the route to be utilized by the Sigchos canton population, fostering tourism and birdwatching activities to generate new income streams while promoting conservation efforts simultaneously.